Commemorative ceremonies Foundation School - solemn Performance - Ego-Aguirre, Ernesto (1956)
On September 9, in the auditorium of the Faculty of Medicine took place with the Performance Solemn ceremonies commemorating the first centenary of his Foundation and attended the Constitutional President of the Republic, Dr. Manuel Prado began.